Precision medicine in colorectal cancer: genomics profiling and targeted treatment - Muradi Muhar, Adi; Velaro, Adrian Joshua; Prananda, Arya Tjipta; Nugraha, Sony Eka; Halim, Princella; Syahputra, Rony Abdi (Frontiers in Pharmacology, 2025)
Precision medicine has revolutionized the treatment of colorectal cancer by enabling a personalized approach tailored to each patient’s unique genetic characteristics. Genomic profiling allows for the identification of specific mutations in genes such as KRAS, BRAF, and PIK3CA, which play a crucial role in cell signaling pathways that regulate cell proliferation, apoptosis, and differentiation. This information enables doctors to select targeted therapies that inhibit specific molecular pathways, maximizing treatment effectiveness and minimizing side effects. Precision medicine also facilitates adaptive monitoring of tumor progression, allowing for adjustments in therapy to maintain treatment effectiveness. While challenges such as high costs, limited access to genomic technology, and the need for more representative genomic data for diverse populations remain, collaboration between researchers, medical practitioners, policymakers, and the pharmaceutical industry is crucial to ensure that precision medicine becomes a standard of care accessible to all. With continued advances and support, precision medicine has the potential to improve treatment outcomes, reduce morbidity and mortality rates, and enhance the quality of life for colorectal cancer patients worldwide.